Community Empowerment in Hypertension Control Through Health Education and Community-Based Early Treatment - Fardi; Sudirman; Fakhrun Nisa (Journal Kiara : Nursing and Midwifery, 2026)
Hypertension is one of the non-communicable diseases that remains a major public health problem because it can lead to serious complications such as heart disease and stroke. Low public awareness and limited knowledge about risk factors and prevention of hypertension causes many cases to remain undetected at an early stage. This community service activity aims to improve community knowledge and awareness in controlling hypertension through community-based health education and blood pressure screening. The method used consisted of preparation, implementation, and evaluation stages. The activity involved 30 participants who had a history of hypertension. The intervention included health education about hypertension, blood pressure examinations, and health consultations for participants with high blood pressure. The results showed an increase in community knowledge after health education, where the proportion of participants with good knowledge increased from 20% to 70%. In addition, participants showed greater awareness of regularly checking their blood pressure and adopting healthier lifestyles. This activity indicates that community-based health education and screening are effective strategies to increase public awareness in hypertension control.